2014
DOI: 10.15343/0104-7809.20143801086097
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da toxicidade de herbicidas usados em cana-de-açúcar para o Paulistinha (Danio rerio)

Abstract: ResumoNa natureza, os organismos são constantemente expostos a mais de um agente tóxico e, apesar do fenômeno de interações químicas ser conhecido há tempos, são poucos os estudos realizados que privilegiam a observação dos efeitos decorrentes da exposição a duas ou mais substâncias. O objetivo deste trabalho foi avaliar o efeito combinado da mistura dos herbicidas Gesapax 500 ® (ametrina 500 g/L)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…According to the classification of Zucker (1985), AMT showed moderately toxicity to tilapia, while DIU+HZN was slightly toxic and TBUT was practically non-toxic. Tesolin et al (2014) working with zebrafish (Danio rerio) embryos exposed to the herbicides AMT and (DIU+HZN) determined the LC 50 ;96h values as, 53.23 ± 3.25 mg L -1 and 37.45 ± 1.741 mg L -1 , respectively. In the present work we observed that tilapia was more sensitive than D. rerio in which both herbicides were slightly toxic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the classification of Zucker (1985), AMT showed moderately toxicity to tilapia, while DIU+HZN was slightly toxic and TBUT was practically non-toxic. Tesolin et al (2014) working with zebrafish (Danio rerio) embryos exposed to the herbicides AMT and (DIU+HZN) determined the LC 50 ;96h values as, 53.23 ± 3.25 mg L -1 and 37.45 ± 1.741 mg L -1 , respectively. In the present work we observed that tilapia was more sensitive than D. rerio in which both herbicides were slightly toxic.…”
Section: Resultsmentioning
confidence: 99%
“…The herbicide diuron revealed a genotoxic potential to Danio rerio, another tropical species, at realistic environmental concentrations (4.3 nM or 1.00233 mg L -1 ) (Bony et al, 2010). In relation to ametryn, Tesolin et al (2014) evaluated the toxicity of the commercial formulation Gesapax 500® (500g L -1 of active ingredient) to D. rerio and concluded that the herbicide was moderately toxic.…”
Section: Introductionmentioning
confidence: 99%
“…The observed deformities were: pericardium oedema, oedema of the yolk sac and a spine deformity showns in figure 5. Such deformities were observed by several authors who studied the toxicity of drugs and some metals: Akande et al (2010); Li et al (2017); Oliveira et al (2009); Oliveira et al (2013); Tesolin et al (2014); Tokunaga et al (2016). All deformations were statistically different from the controls.…”
Section: Short-term Chronic Ecotoxicity Test With Fish Larvaementioning
confidence: 69%
“…Oedema has been one of the malformations most observed in toxicity studies with Danio rerio (Tesolin et al, 2014). The presence of pericardial oedema is due to cardiac dysfunction, functioning as an indicator of osmotic or metabolic dysfunction, frequently associated with extravasations of the endothelial vessels (Dejana et al, 2009;Hallare et al, 2005;Ali et al, 2014) or it is due to renal dysfunction, since the regulation system depends on renal involvement (Coelho, 2004).…”
Section: Short-term Chronic Ecotoxicity Test With Fish Larvaementioning
confidence: 99%
“…It is a filtering organism that feeds on algae, rotifers and infusoria, and plays an important role in the food chain. In addition, its easy cultivation and rapid reproduction make this organism viable for acute and subchronic toxicity experiments (TKACZYK et al 2021;CROA CLUB DE ACUARISMO, 2022) Danio rerio, better known as zebrafish or paulistinha, it is a freshwater fish with approximately five centimeters when adult, with transparent embryos, used in research mainly because it presents an easily observable and testable development (TESOLIN et al, 2014).…”
Section: Introductionmentioning
confidence: 99%